Microplastics in construction and built environment - Lapyote Prasittisopin; Wahid Ferdous; Viroon Kamchoom‬ (Developments in the Built Environment, 2023)
Plastics have been extensively used in the building and construction industries for decades. However, the more plastics are utilised, the more microplastics are released. This review and analysis article summarises and organises the knowledge from 211 current related publications published in 2014–2022. The review and analysis explain the kinds of plastics employed in construction and built environment. Fabrics or textiles, fibres and plastics in cementitious systems, paints, tyres and roads are discussed. The entry points of microplastics into the human body are reviewed next, followed by the management of recycled wastes. The important research gaps and possible solutions include using high-strength concretes and surface-hardening agents is suggested to encapsulate the microplastics inside the matrix; DPSIR model analysis can be holistically adopted for each composite; innovative bio-chemical technology like self-healing concrete and bio-degradable plastics can be a viable choice; and social science, law and urban planning can support awareness and comprehension.
Keywords: Microplastics and Plastic Pollution; Recycling and Waste Management Techniques; Innovations in Concrete and Construction Materials